TWO NEW RECORDS OF ATHYRIUM FOR BALI - Wita Wardani; Bayu Adjie; Kusumadewi Sri Yulita; Andi Salamah (REINWARDTIA, 2022)
WARDANI, W., ADJIE, B., YULITA, K. S. & SALAMAH, A. 2022. Two new records of Athyrium for Bali. Reinwardtia 21(2): 43‒47. — Here we reported two species of Athyrium from Bali for the first time based on herbarium study and field work. We provided morphological description, voucher specimens, and taxonomic note for both species. A key to all the four known species of Athyrium s.l. in Bali was also provided.